"Never give in" : the Italian Resistance and politics - Davidson, Alastair 1939- (Studies in modern European history, 1998)
For a half century, the experience of Resistance has formed a central reference point within the world of Italian politics and culture. The essays that make up "Never Give In" offer a critical assessment both of that legacy and some of the major political forces that have laid claim to it. At the same time, the authors of these essays argue that the Resistance continues as more than simply nostalgia